1981
DOI: 10.1093/nar/9.20.5407
|View full text |Cite
|
Sign up to set email alerts
|

The nucleotide sequence of 5S rRNA from Mycoplasma capricolum

Abstract: The nucleotide sequence of 5S rRNA from Mycoplasma capricoiwn is UUGGUGGUAUAGCAUAGAGGUCACACCUGUUCCCAUGCCGAACACAGAAGUAAGCUCUAUW ACGGUGAAGAUAUW A CUGAUGUGAGAAAAUAGCAAGCUGCCAGUUOH. The length is 107 nucleotides long, and the shortest in all the 5S rRNAs so far known. The sequence is more similar to those of the gram-positive bacteria than those of the gram-negative bacteria. INTRODUCTIONThe mycoplasmas, that have been well known as one of the smallest selfreplicating organisms (1), have a genome of 0.67 x 109 dal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…In the parsimony tree, the pathogenic bacterium Erysipelothrix rhusiopathiae was the closest relative of the mycoplasmas. The observed branching of the mycoplasmas with the low-G+C-content gram-positive eubacteria is consistent with the branching observed previously on 16s and 5s rRNA trees (6,17,20,30,32), the RecA protein sequences (8,18), and a number of other characteristics (20). The fact that different gene and protein sequences, which differ in other important respects (8,12,5,20,30,32), all support a similar evolutionary placement of mycoplasma species strongly indicates that the observed relationship is reliable and that it likely represents the species phylogeny.…”
Section: Lkyn-rs--k-ikhl--nvvnk-g ---N-p---a-lkhfrsrsscgptr ---Sspa--supporting
confidence: 90%
“…In the parsimony tree, the pathogenic bacterium Erysipelothrix rhusiopathiae was the closest relative of the mycoplasmas. The observed branching of the mycoplasmas with the low-G+C-content gram-positive eubacteria is consistent with the branching observed previously on 16s and 5s rRNA trees (6,17,20,30,32), the RecA protein sequences (8,18), and a number of other characteristics (20). The fact that different gene and protein sequences, which differ in other important respects (8,12,5,20,30,32), all support a similar evolutionary placement of mycoplasma species strongly indicates that the observed relationship is reliable and that it likely represents the species phylogeny.…”
Section: Lkyn-rs--k-ikhl--nvvnk-g ---N-p---a-lkhfrsrsscgptr ---Sspa--supporting
confidence: 90%
“…The data for E. coli (22), B. subtilis (23), Lactobacillus brevis (24), Streptococcus faecalis (24), S. cremoris (25), C. pasteurianum (26), Spiroplasma sp. strain BC3 (14), M. capricolum (21), and M. mycoides capri (14) have been reported previously. The residue U has been inserted into position 8 4 and 121.…”
Section: Resultsmentioning
confidence: 86%
“…The three mycoplasma 5S rRNAs previously sequenced (14,21) were reported to be distinctly shorter. The eight mycoplasmas and C. innocuum sequenced in this study were also found to be shorter than typical eubacterial 5S rRNAs.…”
Section: Resultsmentioning
confidence: 96%
“…Hori and colleagues (11) have sequenced the 5S rRNA of Mycoplasma capricolum and have confirmed the close relationship between this species and gram-positive eubacteria. A more extensive phylogenetic analysis of mollicute 5S rRNAs by Rogers and associates (32) was based upon the 5S rRNA sequences of C. innocuum and 10 mollicutes.…”
mentioning
confidence: 85%